Respiratory activity and quality of beet minimally processed - Sanches, Alex Guimarães; Silva, Maryelle Barros da; Moreira, Elaine Gleice Silva; Costa, Jaqueline Macedo; Cordeiro, Carlos Alberto Martins (Scientia Agraria Paranaensis, 2017)
Beet (Beta vulgaris L.) is a tuberous root of great agricultural importance and has been gaining value in the line of minimally processed products. The knowledge of the respiratory behavior and the postharvest quality of this vegetable, due to the processing to which it is submitted, has great importance to prolong its shelflife. The roots were stored for 7 days in a refrigerator at 5 ± 3 ºC and evaluated daily for respiratory rate, ethylene production, soluble solids content, titratable acidity, ascorbic acid content and betalein. All the evaluated characteristics presented influence of the time and the condition of storage, in beet with and withouth processing, on the respiratory pattern and the attributes of quality. In general, the storage of no processed beet guaranteed the best characteristics in all evaluated variables, and in the processed form, the cut in slices maintained the preservation of attributes related to quality, respiratory metabolism and betalinic pigments, being therefore recommended for the processing of this root.